A medical antibacterial fiber and a method for preparing the same
Patent Information
- Application Number
- CN202611311803.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-23
AI Technical Summary
常用壳聚糖亲水性强、易流失且无抗氧化位点;引入普通氧化石墨烯时,因无阳离子杀菌基团、片层易团聚,不仅抑菌谱窄,还会在纤维内形成应力缺陷,导致干湿强显著下降
本发明通过环氧纤维素与己二酸二酰肼之间的开环加成反应,以及改性氧化石墨烯表面醛基与己二酸二酰肼之间的席夫碱缩合反应,协同构建第一重交联网络,同时通过硫辛酸改性壳聚糖与三羟甲基丙烷二烯丙基醚之间的巯基-烯点击反应构建第二重交联网络。两重交联网络相互协同,在纤维内部形成致密的交联结构,提升了纤维的干态断裂强度和湿态断裂强度,同时致密的骨架网络改变了原本松散的结构,为有效防止功能组分的流失提供了坚实的物理基础。通过硫辛酸改性壳聚糖、改性氧化石墨烯的季铵盐基团与己二酸二酰肼的酰肼基团等多重抗菌机制协同作用,赋予纤维优异的抗菌活性,同时双重正交网络成功将大分子抗菌剂牢固锚定在纤维内部,避免了游离抗菌成分的大量析出流失,即便经过50次严苛水洗,纤维依然能保持极高的抗菌率,有效解决了传统抗菌纤维耐洗涤性差的问题。通过在壳聚糖上引入硫辛酸基团,赋予纤维优异的自由基清除能力,并采用改性氧化石墨烯作为功能填料,其表面含有的醛基可作为关键的交联位点参与反应,使得整个纤维的交联网络更加致密,同步实现了物理强度衰减抑制与化学杀菌效能的协同增效,各组分之间的协同增效,使得本发明医用抗菌纤维在医用敷料领域具有广阔的应用前景,能够满足实际应用需求。
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical fiber manufacturing technology, specifically to a medical antibacterial fiber and its preparation method. Background Technology
[0002] Medical dressings need to be applied to broken skin for extended periods, making them prone to attracting pathogens such as Staphylococcus aureus and Escherichia coli. Regenerated cellulose fibers, due to their excellent hydrophilicity and biocompatibility, have become a research hotspot in wound care. However, existing regenerated cellulose-based antibacterial fibers still face the following technical bottlenecks. Most existing products employ physical blending or finishing processes, where antibacterial components are embedded solely by intermolecular forces, lacking a chemical cross-linking network to effectively fix functional components. This leads to significant leaching after washing and soaking in exudate, resulting in rapid attenuation of antibacterial properties. Commonly used chitosan is highly hydrophilic, easily lost, and lacks antioxidant sites. Introducing ordinary graphene oxide, due to the absence of cationic bactericidal groups and the tendency for layer aggregation, not only results in a narrow antibacterial spectrum but also creates stress defects within the fiber, leading to a significant decrease in dry and wet strength. Using hydrazides or olefin cross-linking agents alone is insufficient to balance skeletal rigidity and filler anchoring, making it impossible to achieve a balance between mechanical properties and long-lasting antibacterial effects. For example, patent application CN106929945A discloses a method for preparing porous chitosan. This invention method has a simple preparation process, strong controllability of process conditions, and easy control of material structure and properties. The material has a high specific surface area, strong antibacterial properties, and excellent water absorption and air permeability, and can be used as a medical material. However, this system uses pure chitosan as the fiber-forming matrix and lacks a covalent cross-linking anchoring structure. It is easily dissolved and lost under conditions of wound exudate or repeated water washing, and has insufficient mechanical stability. Moreover, the system does not have antioxidant activity for free radical scavenging, making it difficult to meet the needs of long-term antibacterial and wound antioxidant repair. Summary of the Invention
[0003] In order to overcome the shortcomings of the prior art, the present invention aims to provide a medical antibacterial fiber and its preparation method. The medical antibacterial fiber prepared by the present invention has good mechanical strength, antibacterial properties, water resistance and antioxidant properties.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing medical antibacterial fibers, comprising the following steps: (1) Dissolve 10-12 parts by weight of epoxy cellulose in 80-120 parts by weight of 1-butyl-3-methylimidazolium chloride, and add 1-3 parts by weight of lipoic acid modified chitosan, 0.3-0.5 parts by weight of modified graphene oxide, 2-4 parts by weight of adipic acid dihydrazide and 1-1.5 parts by weight of trimethylolpropane diallyl ether in sequence at 50-60°C. Stir to remove bubbles and obtain homogeneous spinning solution. (2) The homogeneous spinning solution is extruded through a spinneret and then placed in a coagulation bath for solvent exchange to obtain nascent fibers; (3) After the nascent fibers are stretched, they are placed in a slightly acidic crosslinking bath at 70-80℃ with a pH of 5-6 for 1-3 hours to carry out the crosslinking reaction; (4) The cross-linked fiber is washed with water, heat-set and dried to obtain the medical antibacterial fiber.
[0005] Further, in step (1), the preparation method of the epoxy cellulose is as follows: under nitrogen protection, 30-35 mL of 1-butyl-3-methylimidazolium chloride and 3.2-3.4 g of microcrystalline cellulose are added to the reactor and stirred until completely dissolved. Then, at 25-35℃, 0.8-0.9 g of potassium persulfate is added and stirred for 30-40 min. Then, 3-3.1 g of glycidyl methacrylate is added dropwise. After the addition is completed, the reaction is stirred for 3-4 h. After the reaction is completed, the reaction solution is slowly added dropwise to deionized water to precipitate the precipitate. The precipitate is washed and freeze-dried to obtain epoxy cellulose.
[0006] Further, in step (1), the preparation method of the lipoic acid modified chitosan is as follows: 50-60 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 50-60 mL of anhydrous ethanol, and 1-1.2 g of lipoic acid are added to the reactor and stirred at room temperature until completely dissolved. Then, 2.8-2.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is added and stirred until dissolved. Then, 1.6-1.7 g of N-hydroxysuccinimide is added and stirred for 3-4 h. Finally, 0.75-0.8 g of chitosan is added and stirred at room temperature for 22-26 h. After the reaction is completed, the crude product is dialyzed in pure water for 4-5 days, and the dialysate is freeze-dried to obtain lipoic acid modified chitosan.
[0007] Further, in step (1), the method for preparing the modified graphene oxide is as follows: S1: Under nitrogen protection and light-protected conditions, 1-1.1 g of graphene oxide and 6-7 mL of triethylamine were ultrasonically dispersed in 50-60 mL of N,N-dimethylformamide. 10-11 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 0-5℃. The reaction was carried out by stirring at room temperature. The mixture was then washed with N,N-dimethylformamide and deionized water, centrifuged, and vacuum dried to obtain brominated graphene oxide. S2: 0.1-0.2 g of brominated graphene oxide, 1-1.1 g of methacryloyloxyethyltrimethylammonium chloride, 0.08-0.1 g of p-vinylbenzaldehyde, and 60-65 μL of pentamethyldiethylenetriamine are ultrasonically dispersed in 12-15 mL of N,N-dimethylformamide. The reaction system is placed in a complete nitrogen environment by freezing-evacuation-thawing. 85-90 mg of cuprous bromide is added to the system, and the reaction is carried out by stirring at 55-65 °C. The product is washed with N,N-dimethylformamide and centrifuged, and then vacuum dried to obtain modified graphene oxide.
[0008] Furthermore, the reaction time in S1 is 16-24 hours.
[0009] Furthermore, the reaction time in S2 is 22-26 hours.
[0010] Further, in step (3), the slightly acidic crosslinking bath is an acetate buffer or a 2-morpholine ethanesulfonic acid buffer.
[0011] As a specific reaction mechanism of the preparation method of the present invention, in step (3), the crosslinking reaction includes: the disulfide bonds on the chitosan molecular chain modified by lipoic acid undergo thermal homolytic cleavage at 70-80℃, generating sulfur free radical active species in situ; the active species further undergoes an addition reaction with the allyl double bond on the trimethylolpropane diallyl ether molecule, thereby constructing a second crosslinking network. The slightly acidic crosslinking bath may further contain 0.01-0.05% of a thermal initiator (such as azobisisobutyronitrile) of the total mass of the crosslinking bath to promote the above crosslinking reaction.
[0012] The present invention also protects a medical antibacterial fiber, which is prepared by any of the preparation methods described above.
[0013] Compared with the prior art, the present invention has the following beneficial technical effects: This invention synergistically constructs a first crosslinking network through a ring-opening addition reaction between epoxy cellulose and adipic acid dihydrazide, and a Schiff base condensation reaction between aldehyde groups on the surface of modified graphene oxide and adipic acid dihydrazide. Simultaneously, a second crosslinking network is constructed through a mercapto-olefin click reaction between lipoic acid-modified chitosan and trimethylolpropane diallyl ether. These two crosslinking networks work together to form a dense crosslinked structure within the fiber, improving both dry and wet breaking strengths. Furthermore, the dense skeletal network alters the originally loose structure, providing a solid physical basis for effectively preventing the loss of functional components. Through the synergistic effect of multiple antibacterial mechanisms, including lipoic acid-modified chitosan, the quaternary ammonium salt groups of modified graphene oxide, and the hydrazide groups of adipic acid dihydrazide, the fiber is endowed with excellent antibacterial activity. Simultaneously, the dual orthogonal network successfully anchors the macromolecular antibacterial agent firmly within the fiber, preventing the significant release and loss of free antibacterial components. Even after 50 rigorous washes, the fiber maintains an extremely high antibacterial rate, effectively solving the problem of poor wash resistance in traditional antibacterial fibers. By introducing lipoic acid groups onto chitosan, the fiber acquires excellent free radical scavenging capabilities. The use of modified graphene oxide as a functional filler, with its surface aldehyde groups acting as key cross-linking sites, makes the entire fiber's cross-linking network denser. This simultaneously achieves a synergistic effect of inhibiting physical strength decay and enhancing chemical bactericidal efficacy. The synergistic effect among the components makes this invention's medical antibacterial fiber have broad application prospects in the field of medical dressings, meeting practical application needs. Detailed Implementation
[0014] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0015] The reagents used in the following specific embodiments are of analytical grade. Additionally: Microcrystalline cellulose: analytical grade; Chitosan: weight average molecular weight 300,000 g / mol, degree of deacetylation ≥ 90%; Graphene oxide: purity ≥ 95 wt.%, 1 layer, sheet diameter 10 μm, specific surface area 100 m² 2 / g.
[0016] Example 1 (1) Under nitrogen protection, 30 mL of 1-butyl-3-methylimidazole chloride and 3.2 g of microcrystalline cellulose were added to the reactor and stirred until completely dissolved. Then, 0.8 g of potassium persulfate was added at 25 °C and stirred for 30 min. Then, 3 g of glycidyl methacrylate was added dropwise. After the addition was completed, the reaction was stirred for 3 h. After the reaction was completed, the reaction solution was slowly added dropwise to deionized water to precipitate the precipitate. The precipitate was washed and freeze-dried to obtain epoxy cellulose. (2) Add 50 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 50 mL of anhydrous ethanol, and 1 g of thioctic acid to the reactor. Stir at room temperature until completely dissolved. Then add 2.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stir until dissolved. Then add 1.6 g of N-hydroxysuccinimide and stir for 3 h. Finally add 0.75 g of chitosan and stir at room temperature for 22 h. After the reaction is complete, dialyze the crude product in pure water for 4 days. Freeze-dry the dialysate to obtain thioctic acid modified chitosan. (3) Under nitrogen protection and light protection, 1g of graphene oxide and 6mL of triethylamine were ultrasonically dispersed in 50mL of N,N-dimethylformamide. 10mL of bromoisobutyryl bromide was added dropwise under 0℃ ice-water bath conditions. The mixture was stirred at room temperature for 16h. Then it was washed with N,N-dimethylformamide and deionized water and centrifuged. The mixture was then vacuum dried to obtain brominated graphene oxide. (4) 0.1 g of brominated graphene oxide, 1 g of methacryloyloxyethyltrimethylammonium chloride, 0.08 g of p-vinylbenzaldehyde, and 60 μL of pentamethyldiethylenetriamine were ultrasonically dispersed in 12 mL of N,N-dimethylformamide. The reaction system was placed in a complete nitrogen environment by freezing-evacuation-thawing. 85 mg of cuprous bromide was added to it, and the reaction was stirred at 55 °C for 22 h. The product was washed with N,N-dimethylformamide and centrifuged, and then dried under vacuum to obtain modified graphene oxide. (5) Dissolve 10 parts by weight of epoxy cellulose in 80 parts by weight of 1-butyl-3-methylimidazolium chloride, stir at 80°C for 2 hours until completely dissolved, then cool to 50°C, and add 1 part by weight of lipoic acid modified chitosan, 0.3 parts by weight of modified graphene oxide, 2 parts by weight of adipic acid dihydrazide and 1 part by weight of trimethylolpropane diallyl ether in sequence, stir for 1 hour, and degas under vacuum for 30 minutes to obtain homogeneous spinning solution; (6) The homogeneous spinning solution is extruded through a spinneret with a diameter of 0.2 mm and placed in a deionized water coagulation bath at 25°C for solvent exchange. The residence time is 5 min to obtain nascent fibers. (7) The nascent fibers are stretched at a stretch ratio of 2 and then heat-treated in an acetate buffer solution at 70°C with pH 5 for 1 hour to carry out a crosslinking reaction; (8) The cross-linked fiber was washed three times with deionized water, heat-set at 80°C for 30 min, and vacuum-dried at 40°C for 12 h to obtain the medical antibacterial fiber.
[0017] Example 2 (1) Under nitrogen protection, 35 mL of 1-butyl-3-methylimidazole chloride and 3.4 g of microcrystalline cellulose were added to the reactor and stirred until completely dissolved. Then, 0.9 g of potassium persulfate was added at 35 °C and stirred for 40 min. Then, 3.1 g of glycidyl methacrylate was added dropwise. After the addition was completed, the reaction was stirred for 4 h. After the reaction was completed, the reaction solution was slowly added dropwise to deionized water to precipitate the precipitate. The precipitate was washed and freeze-dried to obtain epoxy cellulose. (2) Add 60 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 60 mL of anhydrous ethanol, and 1.2 g of thioctic acid to the reactor. Stir at room temperature until completely dissolved. Then add 2.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride. After stirring and dissolving, add 1.7 g of N-hydroxysuccinimide. Stir for 4 h. Finally, add 0.8 g of chitosan. Stir at room temperature for 26 h. After the reaction is complete, dialyze the crude product in pure water for 5 days. Freeze-dry the dialysate to obtain thioctic acid modified chitosan. (3) Under nitrogen protection and light protection, 1.1 g of graphene oxide and 7 mL of triethylamine were ultrasonically dispersed in 60 mL of N,N-dimethylformamide. 11 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 5 °C. The mixture was stirred at room temperature for 24 h. The mixture was then washed with N,N-dimethylformamide and deionized water and centrifuged. The mixture was then dried under vacuum to obtain brominated graphene oxide. (4) 0.2 g of brominated graphene oxide, 1.1 g of methacryloyloxyethyltrimethylammonium chloride, 0.1 g of p-vinylbenzaldehyde, and 65 μL of pentamethyldiethylenetriamine were ultrasonically dispersed in 15 mL of N,N-dimethylformamide. The reaction system was placed in a complete nitrogen environment by freezing-evacuation-thawing. 90 mg of cuprous bromide was added to it, and the reaction was stirred at 65 °C for 26 h. The product was washed with N,N-dimethylformamide and centrifuged, and then dried under vacuum to obtain modified graphene oxide. (5) Dissolve 12 parts by weight of epoxy cellulose in 120 parts by weight of 1-butyl-3-methylimidazolium chloride, stir at 80°C for 2 hours until completely dissolved, then cool to 60°C, and add 3 parts by weight of lipoic acid modified chitosan, 0.5 parts by weight of modified graphene oxide, 4 parts by weight of adipic acid dihydrazide and 1.5 parts by weight of trimethylolpropane diallyl ether in sequence, stir for 1 hour, and degas under vacuum for 30 minutes to obtain homogeneous spinning solution; (6) The homogeneous spinning solution is extruded through a spinneret with a diameter of 0.2 mm and placed in a deionized water coagulation bath at 25°C for solvent exchange. The residence time is 5 min to obtain nascent fibers. (7) The nascent fibers are stretched at a ratio of 2 and then heat-treated in a 2-morpholine ethanesulfonic acid buffer solution at 80°C with a pH of 6 for 3 hours to carry out a crosslinking reaction; (8) The cross-linked fiber was washed three times with deionized water, heat-set at 80°C for 30 min, and vacuum-dried at 40°C for 12 h to obtain the medical antibacterial fiber.
[0018] Example 3 (1) Under nitrogen protection, 32 mL of 1-butyl-3-methylimidazole chloride and 3.3 g of microcrystalline cellulose were added to the reactor and stirred until completely dissolved. Then, 0.85 g of potassium persulfate was added at 30 °C and stirred for 35 min. Then, 3.05 g of glycidyl methacrylate was added dropwise. After the addition was completed, the reaction was stirred for 3.5 h. After the reaction was completed, the reaction solution was slowly added dropwise to deionized water to precipitate the precipitate. The precipitate was washed and freeze-dried to obtain epoxy cellulose. (2) Add 55 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 55 mL of anhydrous ethanol, and 1.1 g of thioctic acid to the reactor and stir until completely dissolved at room temperature. Then add 2.85 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stir until dissolved. Then add 1.65 g of N-hydroxysuccinimide and stir for 3 h. Finally add 0.78 g of chitosan and stir for 24 h at room temperature. After the reaction is complete, dialyze the crude product in pure water for 4 days and freeze-dry the dialysate to obtain thioctic acid modified chitosan. (3) Under nitrogen protection and light protection, 1.05 g of graphene oxide and 6.5 mL of triethylamine were ultrasonically dispersed in 55 mL of N,N-dimethylformamide. 10.5 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 2 °C. The mixture was stirred at room temperature for 20 h. Then it was washed with N,N-dimethylformamide and deionized water and centrifuged. The mixture was then dried under vacuum to obtain brominated graphene oxide. (4) 0.15 g of brominated graphene oxide, 1.05 g of methacryloyloxyethyltrimethylammonium chloride, 0.09 g of p-vinylbenzaldehyde, and 62 μL of pentamethyldiethylenetriamine were ultrasonically dispersed in 14 mL of N,N-dimethylformamide. The reaction system was placed in a complete nitrogen environment by freezing-evacuation-thawing. 88 mg of cuprous bromide was added to it, and the reaction was stirred at 60 °C for 24 h. The product was washed with N,N-dimethylformamide and centrifuged, and then vacuum dried to obtain modified graphene oxide. (5) Dissolve 11 parts by weight of epoxy cellulose in 100 parts by weight of 1-butyl-3-methylimidazolium chloride, stir at 80°C for 2 hours until completely dissolved, then cool to 55°C, and add 2 parts by weight of lipoic acid modified chitosan, 0.4 parts by weight of modified graphene oxide, 3 parts by weight of adipic acid dihydrazide and 1.2 parts by weight of trimethylolpropane diallyl ether in sequence, stir for 1 hour, and degas under vacuum for 30 minutes to obtain homogeneous spinning solution; (6) The homogeneous spinning solution is extruded through a spinneret with a diameter of 0.2 mm and placed in a deionized water coagulation bath at 25°C for solvent exchange. The residence time is 5 min to obtain nascent fibers. (7) The nascent fibers are stretched at a stretch ratio of 2 and then heat-treated in an acetate buffer solution at pH 5 and 75°C for 2 hours to carry out a crosslinking reaction; (8) The cross-linked fiber was washed three times with deionized water, heat-set at 80°C for 30 min, and vacuum-dried at 40°C for 12 h to obtain the medical antibacterial fiber.
[0019] Example 4 (1) Under nitrogen protection, 32 mL of 1-butyl-3-methylimidazolium chloride and 3.25 g of microcrystalline cellulose were added to the reactor and stirred until completely dissolved. Then, 0.82 g of potassium persulfate was added at 28 °C and stirred for 32 min. Then, 3.08 g of glycidyl methacrylate was added dropwise. After the addition was completed, the reaction was stirred for 4 h. After the reaction was completed, the reaction solution was slowly added dropwise to deionized water to precipitate the precipitate. The precipitate was washed and freeze-dried to obtain epoxy cellulose. (2) Add 52 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 58 mL of anhydrous ethanol, and 1.05 g of thioctic acid to the reactor and stir until completely dissolved at room temperature. Then add 2.88 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stir until dissolved. Then add 1.62 g of N-hydroxysuccinimide and stir for 3 h. Finally add 0.76 g of chitosan and stir for 23 h at room temperature. After the reaction is complete, dialyze the crude product in pure water for 5 days and freeze-dry the dialysate to obtain thioctic acid modified chitosan. (3) Under nitrogen protection and light protection conditions, 1.08 g of graphene oxide and 6.8 mL of triethylamine were ultrasonically dispersed in 52 mL of N,N-dimethylformamide. 10.2 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 2 °C. The mixture was stirred at room temperature for 18 h. Then, the mixture was washed with N,N-dimethylformamide and deionized water and centrifuged. The mixture was then dried under vacuum to obtain brominated graphene oxide. (4) 0.16 g of brominated graphene oxide, 1.04 g of methacryloyloxyethyltrimethylammonium chloride, 0.08 g of p-vinylbenzaldehyde, and 64 μL of pentamethyldiethylenetriamine were ultrasonically dispersed in 13 mL of N,N-dimethylformamide. The reaction system was placed in a complete nitrogen environment by freezing-evacuation-thawing. 86 mg of cuprous bromide was added to it, and the reaction was stirred at 58 °C for 24 h. The product was washed with N,N-dimethylformamide and centrifuged, and then vacuum dried to obtain modified graphene oxide. (5) Dissolve 11 parts by weight of epoxy cellulose in 90 parts by weight of 1-butyl-3-methylimidazolium chloride, stir at 80°C for 2 hours until completely dissolved, then cool to 55°C, and add 2 parts by weight of lipoic acid modified chitosan, 0.3 parts by weight of modified graphene oxide, 3 parts by weight of adipic acid dihydrazide and 1 part by weight of trimethylolpropane diallyl ether in sequence, stir for 1 hour, and degas under vacuum for 30 minutes to obtain homogeneous spinning solution; (6) The homogeneous spinning solution is extruded through a spinneret with a diameter of 0.2 mm and placed in a deionized water coagulation bath at 25°C for solvent exchange. The residence time is 5 min to obtain nascent fibers. (7) The nascent fibers were stretched at a stretch ratio of 2 and then heat-treated in an acetate buffer solution at pH 5 and 73°C for 2 hours to carry out a crosslinking reaction. (8) The cross-linked fiber was washed three times with deionized water, heat-set at 80°C for 30 min, and vacuum-dried at 40°C for 12 h to obtain the medical antibacterial fiber.
[0020] Example 5 (1) Under nitrogen protection, 34 mL of 1-butyl-3-methylimidazolium chloride and 3.35 g of microcrystalline cellulose were added to the reactor and stirred until completely dissolved. Then, 0.85 g of potassium persulfate was added at 32 °C and stirred for 35 min. Then, 3.08 g of glycidyl methacrylate was added dropwise. After the addition was completed, the reaction was stirred for 3 h. After the reaction was completed, the reaction solution was slowly added dropwise to deionized water to precipitate the precipitate. The precipitate was washed and freeze-dried to obtain epoxy cellulose. (2) Add 52 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 55 mL of anhydrous ethanol, and 1.15 g of thioctic acid to the reactor and stir until completely dissolved at room temperature. Then add 2.85 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and stir until dissolved. Then add 1.68 g of N-hydroxysuccinimide and stir for 4 h. Finally add 0.78 g of chitosan and stir for 25 h at room temperature. After the reaction is complete, dialyze the crude product in pure water for 5 days and freeze-dry the dialysate to obtain thioctic acid modified chitosan. (3) Under nitrogen protection and light protection, 1.08 g of graphene oxide and 6.2 mL of triethylamine were ultrasonically dispersed in 52 mL of N,N-dimethylformamide. 10.8 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 4 °C. The mixture was stirred at room temperature for 22 h. The mixture was then washed with N,N-dimethylformamide and deionized water and centrifuged. The mixture was then vacuum dried to obtain brominated graphene oxide. (4) 0.18 g of brominated graphene oxide, 1.08 g of methacryloyloxyethyltrimethylammonium chloride, 0.1 g of p-vinylbenzaldehyde, and 64 μL of pentamethyldiethylenetriamine were ultrasonically dispersed in 14 mL of N,N-dimethylformamide. The reaction system was placed in a complete nitrogen environment by freezing-evacuation-thawing. 88 mg of cuprous bromide was added to it, and the reaction was stirred at 65 °C for 25 h. The product was washed with N,N-dimethylformamide and centrifuged, and then vacuum dried to obtain modified graphene oxide. (5) Dissolve 11 parts by weight of epoxy cellulose in 110 parts by weight of 1-butyl-3-methylimidazolium chloride, stir at 80°C for 2 hours until completely dissolved, then cool to 50°C, and add 3 parts by weight of lipoic acid modified chitosan, 0.5 parts by weight of modified graphene oxide, 3 parts by weight of adipic acid dihydrazide and 1.5 parts by weight of trimethylolpropane diallyl ether in sequence, stir for 1 hour, and degas under vacuum for 30 minutes to obtain homogeneous spinning solution; (6) The homogeneous spinning solution is extruded through a spinneret with a diameter of 0.2 mm and placed in a deionized water coagulation bath at 25°C for solvent exchange. The residence time is 5 min to obtain nascent fibers. (7) The nascent fibers are stretched at a ratio of 2 and then heat-treated in a 2-morpholine ethanesulfonic acid buffer solution at 80°C with a pH of 6 for 3 hours to carry out a crosslinking reaction; (8) The cross-linked fiber was washed three times with deionized water, heat-set at 80°C for 30 min, and vacuum-dried at 40°C for 12 h to obtain the medical antibacterial fiber.
[0021] Comparative Example 1 The main difference between this comparative example and Example 5 is that an equal weight of microcrystalline cellulose is used instead of epoxy cellulose, while the remaining preparation steps and parameters are the same as in Example 5.
[0022] Comparative Example 2 The main difference between this comparative example and Example 5 is that chitosan of equal weight is used instead of thioctic acid-modified chitosan, while the other preparation steps and parameters are the same as in Example 5.
[0023] Comparative Example 3 The main difference between this comparative example and Example 5 is that an equal part by weight of graphene oxide is used instead of modified graphene oxide, while the remaining preparation steps and parameters are consistent with those of Example 5.
[0024] Comparative Example 4 The main difference between this comparative example and Example 5 is that adipic dihydrazide is not added, while the rest of the preparation steps and parameters are the same as in Example 5.
[0025] Comparative Example 5 The main difference between this comparative example and Example 5 is that trimethylolpropane diallyl ether is not added, while the remaining preparation steps and parameters are consistent with those of Example 5.
[0026] Performance testing The medical antibacterial fibers prepared in Examples 1-5 and Comparative Examples 1-5 were subjected to performance tests.
[0027] (1) Fracture strength test Dry breaking strength: The breaking strength of each sample was tested according to GB / T 14337-2022 "Test Method for Tensile Properties of Chemical Fibers Short Fibers". Each sample was tested 10 times, and the average value was recorded. Wet breaking strength: After soaking the fiber in deionized water for 24 hours, remove it, absorb the surface moisture with filter paper, and immediately test the wet breaking strength according to the same standard.
[0028] (2) Antibacterial performance test The fibers are opened, combed, web-laid, and needle-punched to achieve a weight of 400 g / m². 2 The nonwoven fabric was tested for its antibacterial rate against Escherichia coli (ATCC25922) and Staphylococcus aureus (ATCC6538) in accordance with GB / T20944.3-2008 "Evaluation of antimicrobial properties of textiles - Part 3: Shaking method". Each sample was tested three times, and the average value was recorded.
[0029] (3) Water wash resistance test The fibers were washed 50 times according to the washing procedure of AATCC 61-2013 "Textiles - Accelerated Method for Color Fastness to Household and Commercial Washing". The antibacterial rate was then tested according to GB / T 20944.3-2008 "Evaluation of Antimicrobial Properties of Textiles - Part 3: Shaking Method" and the data were recorded.
[0030] (4) Antioxidant activity test Cut the fiber into 5mm×5mm pieces. Take 0.1g of fiber and immerse it in 10mL of 0.1mmol / L DPPH ethanol solution. React at room temperature in the dark for 30min. Measure the change in absorbance at 517nm. Calculate the free radical scavenging rate using the following formula: Scavenging rate (%) = (1-A1 / A0)×100, where A0 is the absorbance of the blank control group measured after mixing 10mL of 0.1mmol / L DPPH ethanol solution with an equal volume of pure ethanol and reacting at room temperature in the dark for 30min, and A1 is the absorbance of the sample group.
[0031] The test results are shown in Table 1.
[0032] Table 1: Performance Tests Example 1 3.12 2.45 99.1 99.3 95.2 96.0 87.2 Example 2 3.28 2.61 99.4 99.6 96.0 96.8 90.6 Example 3 3.21 2.54 99.3 99.5 95.6 96.3 89.1 Example 4 3.15 2.48 99.2 99.4 95.4 96.1 88.5 Example 5 3.35 2.68 99.5 99.7 97.3 97.8 91.3 Comparative Example 1 2.03 1.16 81.2 83.6 66.8 68.5 38.5 Comparative Example 2 3.08 2.39 90.5 92.1 53.1 55.6 11.2 Comparative Example 3 2.46 1.62 86.1 88.5 80.2 82.4 42.8 Comparative Example 4 2.52 1.70 99.0 99.2 69.8 72.1 90.8 Comparative Example 5 2.18 1.35 99.4 99.6 58.4 61.2 91.1 As can be seen from Table 1, the medical antibacterial fibers prepared in Examples 1-5 have good mechanical strength, antibacterial properties, water resistance and antioxidant properties.
[0033] The comparison shows that Comparative Example 1 used microcrystalline cellulose instead of epoxy cellulose, and Comparative Example 4 did not add adipic acid dihydrazide. Due to the lack of epoxy groups or hydrazide groups in the system, the ring-opening addition and Schiff base condensation reaction could not occur, and the macroscopic skeleton network of the fiber could not be effectively cross-linked. Therefore, the dry and wet breaking strength of these two groups decreased significantly. Moreover, due to the loose structure, the functional components were severely lost, resulting in a significantly lower antibacterial rate after washing compared to the example. In particular, Comparative Example 1 had a significantly lower DPPH scavenging rate (38.5%) than the example due to the loose overall structure and severe loss of antioxidant functional components. Although Comparative Example 4 retained a high free antioxidant activity (90.8%), it lost the long-term anchoring basis. Comparative Example 2 used unmodified chitosan instead of lipoic acid-modified chitosan, and Comparative Example 5 did not add trimethylolpropane diallyl ether. Both of these groups lacked the necessary groups for the thiol-ene click reaction, making it impossible to construct a second cross-linking network. Although Comparative Example 5 had a high initial antibacterial rate, after 50 rigorous water washes, a large amount of free antibacterial components were released and lost, causing the antibacterial rate to drop to around 60%. Comparative Example 2 not only had an extremely low antibacterial rate after washing, but also, due to the lack of lipoic acid, its DPPH free radical scavenging rate was only 11.2%. Comparative Example 3 used unmodified ordinary graphene oxide instead of modified graphene oxide. Because the surface of ordinary graphene oxide lacked quaternary ammonium salt groups that provide chemical bactericidal effects and aldehyde groups that provide cross-linking sites, the fiber's initial antibacterial rate not only decreased to around 86%, but the cross-linking network was also not dense enough due to the lack of key nodes, resulting in a significant decrease in both dry and wet breaking strength and antioxidant activity.
[0034] It should be noted that, in this document, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitation, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.
[0035] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
[0036] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments.
Claims
1. A method for preparing medical antibacterial fibers, characterized in that, Includes the following steps: (1) Dissolve 10-12 parts by weight of epoxy cellulose in 80-120 parts by weight of 1-butyl-3-methylimidazolium chloride, and add 1-3 parts by weight of lipoic acid modified chitosan, 0.3-0.5 parts by weight of modified graphene oxide, 2-4 parts by weight of adipic acid dihydrazide and 1-1.5 parts by weight of trimethylolpropane diallyl ether in sequence at 50-60°C. Stir to remove bubbles and obtain homogeneous spinning solution. (2) The homogeneous spinning solution is extruded through a spinneret and then placed in a coagulation bath for solvent exchange to obtain nascent fibers; (3) After the nascent fibers are stretched, they are placed in a slightly acidic crosslinking bath at 70-80℃ with a pH of 5-6 for 1-3 hours to carry out the crosslinking reaction; (4) The cross-linked fiber is washed with water, heat-set and dried to obtain the medical antibacterial fiber.
2. The method for preparing medical antibacterial fibers according to claim 1, characterized in that, In step (1), the preparation method of the epoxy cellulose is as follows: under nitrogen protection, 30-35 mL of 1-butyl-3-methylimidazolium chloride and 3.2-3.4 g of microcrystalline cellulose are added to the reactor and stirred until completely dissolved. Then, at 25-35℃, 0.8-0.9 g of potassium persulfate is added and stirred for 30-40 min. Then, 3-3.1 g of glycidyl methacrylate is added dropwise. After the addition is complete, the reaction is stirred for 3-4 h. After the reaction is completed, the reaction solution is slowly added dropwise to deionized water to precipitate the precipitate. The precipitate is washed and freeze-dried to obtain epoxy cellulose.
3. The method for preparing medical antibacterial fibers according to claim 1, characterized in that, In step (1), the preparation method of the lipoic acid modified chitosan is as follows: 50-60 mL of morpholine ethanesulfonic acid buffer with a concentration of 0.1 mol / L and a pH of 5.5, 50-60 mL of anhydrous ethanol, and 1-1.2 g of lipoic acid are added to the reactor and stirred at room temperature until completely dissolved. Then, 2.8-2.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is added and stirred until dissolved. Then, 1.6-1.7 g of N-hydroxysuccinimide is added and stirred for 3-4 h. Finally, 0.75-0.8 g of chitosan is added and stirred at room temperature for 22-26 h. After the reaction is completed, the crude product is dialyzed in pure water for 4-5 days, and the dialysate is freeze-dried to obtain the lipoic acid modified chitosan.
4. The method for preparing medical antibacterial fibers according to claim 1, characterized in that, In step (1), the modified graphene oxide is prepared by: S1: Under nitrogen protection and light-protected conditions, 1-1.1 g of graphene oxide and 6-7 mL of triethylamine were ultrasonically dispersed in 50-60 mL of N,N-dimethylformamide. 10-11 mL of bromoisobutyryl bromide was added dropwise under ice-water bath conditions at 0-5℃. The reaction was carried out by stirring at room temperature. The mixture was then washed with N,N-dimethylformamide and deionized water, centrifuged, and vacuum dried to obtain brominated graphene oxide. S2: 0.1-0.2 g of brominated graphene oxide, 1-1.1 g of methacryloyloxyethyltrimethylammonium chloride, 0.08-0.1 g of p-vinylbenzaldehyde, and 60-65 μL of pentamethyldiethylenetriamine are ultrasonically dispersed in 12-15 mL of N,N-dimethylformamide. The reaction system is placed in a complete nitrogen environment by freezing-evacuation-thawing. 85-90 mg of cuprous bromide is added to the system, and the reaction is carried out by stirring at 55-65 °C. The product is washed with N,N-dimethylformamide and centrifuged, and then vacuum dried to obtain modified graphene oxide.
5. The method for preparing medical antibacterial fibers according to claim 4, characterized in that, The reaction time in S1 is 16-24 hours.
6. The method for preparing medical antibacterial fibers according to claim 4, characterized in that, The reaction time in S2 is 22-26 hours.
7. The method for preparing medical antibacterial fibers according to claim 1, characterized in that, In step (3), the slightly acidic crosslinking bath is an acetate buffer or a 2-morpholine ethanesulfonic acid buffer.
8. A medical antibacterial fiber, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Preparation method of porous anti-microbial chitosan medical fiber
CN106929945A